La identidad cuestionada: un comerciante francés en el golfo de California en 1830 - Dení Trejo Barajas (Centre de Recherches sur les Mondes Américains, 2019)
This paper examines the French traveler Cyprien Combier´s journey reaching the coasts of Sonora and Sinaloa (Mexico). Particularly, in this text I analyze the way Combier describes his reactions when contact is made with the indigenous people of that area. This has allowed me to recognize that West self-affirmation facing the American world has not always been considered as spotless. Europeans’ assumed superiority – their honorability, their ability as business entrepreneurs, as well as the possession of a myriad of objects that granted them comfort – was questioned when it faced the American realities of the “noble savage” – assertion shared by the Europeans –. The appreciation of the life of the Americans led them to question, appreciate and have a longing, although inconstant, for the “misery” of the Other, who, apparently “has nothing but is happy”.